An Economic Analysis of Monetary Policy in Four ASEAN Economies - Tan, Siow Hooi (2005)
Asymmetric effect, in the context of monetary policy, refers to a situation in which the effects of a given policy are not constant but vary depending on the circumstances. By employing a relatively popular technique of non-linear modelling - for instance, Hamilton's Markov-switching model - this study empirically analyses if real output asymmetrically responds to monetary policy shocks in four ASEAN economies: Indonesia, Malaysia, the Philippines and Thailand. Typically, the asymmetries in discussion are pertaining to, (i) the policy action and, (ii) the phase of the business cycle. Quarterly data spanning the period from 1978: 1 for Indonesia; 1974:l for Malaysia; 1977:l for the Philippines and Thailand; to 2003:4 are being utilised in this study. Several important observations can be made based on this study. First, this study provides evidence that a tight monetary policy has a larger absolute impact than an easy policy. For instance, by incorporating a time-varying inflation parameter in the model, both the money supply shocks and interest rate shocks in all economies under study are found to have asymmetric effects on real output, in which the effects of an easy policy mitigate while the effects of a tight policy increase, with higher inflation rates. Furthermore, the inverted L-shaped aggregate supply curve and negative-sloped equilibrium locus is supported in the case of Indonesia, the Philippines and Thailand. This evidence implies that an easy policy has a favourable impact, no impact and a harmful impact on output during the low, medium and high inflation regimes respectively in these economies. The fact of asymmetry is particularly important in the Asian context in their discussion and formulation for a monetary union. It implies that monetary authorities must take into account not only the fact that these economies do not react symmetrically in response to the policy action but also the behaviour of the inflation process. In other words, the evidence of high inflation rates for some of the developing economies may contribute to increased asymmetries in this context. Second, the results do support the argument that effects of monetary policy vary depending on the phase of the business cycle. More precisely, monetary policy effects are found to be larger during recessionary periods for all economies under study. This finding therefore suggests the important role that credit market imperfections have on a firm's investment behaviour, which in turn points to the financial accelerator as a relevant mechanism underlying the observed asymmetry. An important lesson based on this study is that the macroeconomic stability will be in dire peril if financial systems of these economies are not managed prudently. Policies thus may be designed to reduce the financial sector's vulnerability to a crisis by encouraging appropriate and disciplined financial intermediary practices.